2017
DOI: 10.1002/bab.1588
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing recombinant interleukin‐6 production yield by fermentation optimization, two‐step denaturing, and one‐step purification

Abstract: Interleukin-6 a pleiotropic cytokine involved in a wide range of biological activities. So the large-scale production of biologically active recombinant human interleukin-6 is important for its structural and functional studies. Here, we report an optimized method for shake flask fermentation and a simplified high-yield purification procedure for the recombinant interleukin-6. This high-yield expression method not only involves the optimization of the fermentation condition but also the single step purificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…As aging progresses, the immune system of the liver further changes, exhibiting distinct inflammation. Simultaneously, immune cell infiltration is increased [ 25 ], which increases the number of lymphocytes, resulting in an increased expression of the proinflammatory cytokines, including interferon-gamma (IFN- γ ), interleukin-beta (IL- β ), IL-6, tumor necrosis factor-alpha (TNF- α ), and IL-2, and the anti-inflammatory cytokines, which include transforming growth factor-beta (TGF- β ) and IL-10 [ 26 29 ] ( Figure 2 ). Singh et al found that the elevated levels of IFN- γ in the aging liver lead to phosphorylation of STAT1 (an H3 deacetylase that upregulates the postoperative levels of glucose (Glu) and triglycerides (TG), which play an essential role in liver regeneration), which activates p21 protein that inhibits cyclin-dependent kinases (CDKs), thereby inhibiting cell cycle progression [ 30 ].…”
Section: The Immune System and Regeneration Of The Aging Livermentioning
confidence: 99%
“…As aging progresses, the immune system of the liver further changes, exhibiting distinct inflammation. Simultaneously, immune cell infiltration is increased [ 25 ], which increases the number of lymphocytes, resulting in an increased expression of the proinflammatory cytokines, including interferon-gamma (IFN- γ ), interleukin-beta (IL- β ), IL-6, tumor necrosis factor-alpha (TNF- α ), and IL-2, and the anti-inflammatory cytokines, which include transforming growth factor-beta (TGF- β ) and IL-10 [ 26 29 ] ( Figure 2 ). Singh et al found that the elevated levels of IFN- γ in the aging liver lead to phosphorylation of STAT1 (an H3 deacetylase that upregulates the postoperative levels of glucose (Glu) and triglycerides (TG), which play an essential role in liver regeneration), which activates p21 protein that inhibits cyclin-dependent kinases (CDKs), thereby inhibiting cell cycle progression [ 30 ].…”
Section: The Immune System and Regeneration Of The Aging Livermentioning
confidence: 99%
“…The sole expression of recombinant IL-17A or IL-6 in E. coli generated only clear bands for the insoluble material after extracting the isopropyl-β- d -thiogalactoside (IPTG)-induced cells (indicated by white arrows), and this observation confirmed previous studies wherein both the proteins are largely produced in the form of inactive IBs in E. coli . 3,14 Also, our unsuccessful efforts to purify them from the cell lysates using Ni immobilized metal-ion affinity chromatography (Ni–IMAC) supports the difficulties in obtaining these properly folded proteins (data not shown). Most likely, the incorrect disulfide bond formation by mispairing of cysteines within these two cytokines caused the inappropriate folding and assembly of the ILs.…”
mentioning
confidence: 91%
“…containing multiple disulfide bonds), the operational process of refolding is always cumbersome and time-consuming, which leads to considerable yield losses and accounts for a major cost in the protein production process. 2,3 Thus, the formation of IBs imposes a great hurdle in the production of recombinant proteins in E. coli . Fusion tags (MBP, GST, etc. )…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Expanding upon these foundational studies, this study presents an advancement with the successful implementation of a cascaded-mixer system, enabling FMR-mode protein refolding. We studied the conformational changes of the cytokine interleukin (IL-)6 as a model, 18 at different pH and in various organic solvents 19,20 to determine the most effective way to generate the optimal IL-6 conformation. IL-6 has an α-helixrich structure and tends to dimerize and aggregate, making it a suitable model.…”
Section: ■ Introductionmentioning
confidence: 99%